Evaluation of Medical Internet Sites - Adelhard, K.; Obst, O. (Methods of Information in Medicine, 1999)
A huge amount of medical information is available on the Internet for both experts and laypersons. These resources are frequently used to answer current medical questions and are thus likely to influence the behavior of the users. Criteria for assessing the quality of medical Internet resources have been established by a number of authors and institutions to provide reliable medical information on the Internet for both patients and physicians. Clinical studies on the impact of information on the Internet are still lacking. The next step is to evaluate the outcome of such information services and to prove that they affect health-related parameters. Due to different constraints, classical strategies of controlled clinical trials can only be partly applied. New methods have to be developed and validated in practice.
Keywords: Internet; Evaluation; Quality of Information